The Impact of Reward Systems and Employee Training on Work Effectiveness Improvement in Micro, Small, and Medium Enterprises (MSMEs): A Case Study of Mie Besty - Vina Rohmatul Ummah; Malika Risqi; Indra Lukmanul Khakim; Muhammad Alkirom Wildan (Badan Penerbit STIEPARI Press, 2025)
In an increasingly competitive business environment, employee performance effectiveness is one of the key factors determining the success of micro, small, and medium enterprises (MSMEs). This study aims to analyze the impact of the reward system and training on employee performance at MSME Mie Besty using a qualitative approach through interviews and observations. The findings indicate that implementing a reward system, both financial (such as salary, bonuses, and incentives) and non-financial (such as recognition, promotions, and workplace facilities), significantly enhances employee motivation and productivity. Additionally, training programs covering technical skills, customer service, and operational management contribute to improving employee competencies and work efficiency. The synergy between the reward system and training fosters a more conducive work environment, increases job satisfaction, and reduces employee turnover rates. Thus, this study emphasizes that the combination of reward strategies and training can serve as an effective solution for improving employee performance in the MSME sector. Therefore, MSMEs are encouraged to implement fair and transparent reward policies and develop continuous training programs to enhance business competitiveness and long-term sustainability.